HASIL BELAJAR KETERAMPILAN KOGNITIF FISIKA MELALUI PENERAPAN PENDEKATAN KONSTRUKTIVISME PADA SISWA KELAS X1 SMA NEGERI 1 TAMBANG - Yennita Yennita; Ratih Ika Tiswari; Zuhdi Ma’aruf (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2007)
The purpose of this research is to describe the result of students cognitive skill or competent throughan approach of constructivism by learning of physics. The subjects of this research are student class X1, fromSMAN 1 Tambang in academic year 2006/2007. The totals of students are 41 students who are consist of 20men and 21 women. The instrument of collecting this data is about result of student’s cognitive skill.Collecting of this data is in the end of learning process with hold a cognitive skill test. Data will be analyzeby using descriptive analyze with includes are abortive powers, learning effectiveness, completeness ofstudent’s study and completeness of learns purpose. The result of data analysis shows average of student’sabortive power is 75, 5% with good’s category, learning effectiveness is 75, 9% with effective enough’scategory, completeness of student’s study classically is 81, 5% with uncompleted category and completenessof learns purpose classically is 90,9% with complete category. However, approach of constructivism appliesto dynamic electricity material that effective enough for learning of physic in SMAN 1 Tambang.Key words: approach of constructivism, result of cognitive study